(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article presents the results of the research carried out in order to update and restore the fertility of the collection samples of sweet potato (Ipomoea batatas), Jerusalem artichoke (Helianthus tuberosus) and garlic onion (Allium sativum) belonging to vegetatively reproducing vegetable crops stored in the gene pool.